Effect of notch depth on fracture toughness of zirconia ceramics tested by SEVNB method. Issue 14 (1st October 2018) - Cui, Jinping; Gong, Zhenyuan; Lv, Ming; Rao, Pinggen
Abstract: Ultra sharp V-notches with different depth to width ratio (a/w) were prefabricated on test bars by diamond wheel and femtosecond laser to measure the fracture toughness of 1.5Y/3Ca/6.5Al/1.5Si-PSZ, 2.5Y-TZP, 3Y-TZP and 8Y-FSZ ceramics by single-edge V-notched beam (SEVNB) method. For comparison, the fracture toughness of Al2 O3 ceramics was also determined. Based on the analyses of SEM and XRD, the different microstructures and phase transformability led the plateau fracture toughness values of the investigated samples to vary from 1.6 to 9.4 MPa m 1/2 . The relationship between the a/w value and the plateau fracture toughness has been established.